Reconfiguring Politics, Law, and Human Rights in the Contemporary Muslim World (American Journal of Islam and Society, 2011)
In the final decades of the twentieth century, a new strand of Islamic intellectualismbegan inserting itself into contemporary Muslim discourses onpolitics, law, and human rights. Not fitting into existing neat categoriessuch as traditionalist, revivalist, and modernist-liberal Islam, its promotersoperate on the interstices of established traditions and practices within theMuslim world, as well as the liminal spaces between cultures and civilizations.With the advent of the new millennium, the impact of their alternative, cosmopolitan or culturally hybrid ways of engaging with the Islamicheritage, or turath, is receiving increasing recognition.In his latest book, Religion and Politics in the Middle East, which examineswhether religion has primacy over politics or the other way around,Robert D. Lee’s focus has shifted from individuals (Muhammad Iqbal,Sayyid Qutb, Ali Shariati, and Mohammed Arkoun) to a quartet of countries(Egypt, Israel, Turkey, and Iran). At the same time, he continues toacknowledge the significance of maverick thinkers such as the EgyptianNasr Hamid Abu Zayd, Turkey’s Said Nursi and Fethullah Gülen, and theIranian Abdolkarim Soroush and Mohsen Kadivar in questioning, challenging,and transforming the intellectual and political scenes in their respectivecountries and beyond—although often forced to do so from abroad asexilic intellectuals ...